D'un carnet l'autre : Personne et personnage chez Marcel Arland - Pardo Jiménez, Pedro (Verbum – Analecta Neolatina, 2016)
In Carnets de Gilbert (1931), Marcel Arland gives voice again to the hero of L'Ordre, the novel for which he had been awarded the Goncourt Prize two years before. The novel consists of a collection of intimate reflections where Gilbert, alter ego of Arland in his fiction, expresses – in first person this time – the typical pessimism of postwar French youth. The notably enhanced 1944 reedition of the work turns to the same subject but adopts a deeper perspective and a more elaborate discourse. Ultimately, what this evolution shows is that, despite the coincidence in the title, the view of the world in Carnets de Gilbert of 1944 is no longer the character’s but the author’s.